2011
DOI: 10.1039/c0cc03993d
|View full text |Cite
|
Sign up to set email alerts
|

A switchable fluorescent quantum dot probe based on aggregation/disaggregation mechanism

Abstract: Here we report a facile switchable fluorescent QD probe for F(-) ions, which is based on the hydrogen bonding-driven aggregation and the analyte-triggered disaggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 30 publications
4
73
0
Order By: Relevance
“…Fluoride plays various important roles in environmental, industrial and biological processes and the ability to sense fluoride has attracted increasing attention [94]. By utilizing the disassemble procedure, we have developed a facile switchable fluorescent QD probe for F − ions [95]. As shown in Figure 4, the cysteamine capped CdTe QDs undergo spontaneous self-aggregation via NH-N hydrogen bonds, which results in efficient fluorescence self-quenching due to energy transfer mechanism.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Fluoride plays various important roles in environmental, industrial and biological processes and the ability to sense fluoride has attracted increasing attention [94]. By utilizing the disassemble procedure, we have developed a facile switchable fluorescent QD probe for F − ions [95]. As shown in Figure 4, the cysteamine capped CdTe QDs undergo spontaneous self-aggregation via NH-N hydrogen bonds, which results in efficient fluorescence self-quenching due to energy transfer mechanism.…”
Section: Figurementioning
confidence: 99%
“…(1) Self-aggregation due to internanoparticle hydrogen bonding interaction; (2) disaggregation due to the substitution of hydrogen bonds[95].…”
mentioning
confidence: 99%
“…Cysteamine can provide a short inter particle distance, which is essential for effective aggregation (Liu et al, 2011).…”
Section: The Detection Principle Of Aptasensormentioning
confidence: 99%
“…Recently, some studies reported that fluorescence intensity of QDs was quenched at closer distance via the interaction such as van der Waals attraction [13], hydrogen bonding [14], or covalent binding [15]. Fluorescence intensity recovered or increased when QDs disaggregated with longdistance interval [14].…”
Section: Introductionmentioning
confidence: 98%